EFFECTIVENESS OF EARLY MOBILIZATION, EARLY BREASTFEEDING INITIATION, AND OXYTOCIN MASSAGE AGAINST UTERINE INVOLUTION - Yanyan Mulyani; Iis Solihah (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
The puerperium begins after the birth of the placenta and ends when the uterine uterus returns to normal. During this period, two important events happened, namely uterine involution and lactation. Uterine involution is very important to stop the hemorrhage. The purpose of this study was to determine the factors of early mobilization, Early Breastfeeding Initiation, Oxytocin Massage against uterine involution in puerperal women at Community Health Center of Solokan Jeruk. This study used a quasi-experimental approach —46 samples taken using inclusion and exclusion criteria. Data analyzed using the chi-square test with ɑ = 0.05. The study showed that there is a significant correlation between early mobilization (p-value =0.001), Early Breastfeeding Initiation (IMD) P (p-value= 0.032), and oxytocin massage (p-value= 0.006) against uterine involution in puerperal women at Puskesmas Solokan Jeruk. To Optimize the process, it needs adequate obstetrical care. Keywords: Early Mobilization, Early Breastfeeding Initiation, Oxytocin Massage, Uterine Involution